Nabataean trade deities - Alrehaili, Rawan Faisal; Alabdaljabbar, Abdullah Abdulrahman (Journal of Humanities & Social Sciences, 2024)
This research delves into the significance of religion in the Nabataean civilization. It highlights how religion permeated various aspects of Nabataean life and commerce, evident in their temples, beliefs, and rituals. The strategic placement of Nabataean temples along trade routes and in distant regions underscores their profound connection to religion and the Nabataean pantheon of deities. Remarkably, this religious commitment remained unwavering despite their active involvement in economic activities and long-distance trade. Additionally, the discovery of temples and inscriptions along the Mediterranean coast, dedicated to deities associated with Nabataean merchant communities, attests to the wide-reaching influence of Nabataean religious practices beyond their territorial boundaries. Notably, the Nabataeans exhibited an open-minded approach to incorporating deities from the commercial regions they engaged with. Their extensive trade interactions with various ancient cultures led to the assimilation of additional deities into their belief system. This adaptive process resulted in the expansion of attributes and roles attributed to Nabataean deities, alterations in their names, and the incorporation of symbolic elements within Nabataean temples. Despite this, scholarly literature on Nabataean deities, their distinctive characteristics, and their role in the Nabataean trade remain notably scarce, particularly in comparison to deities from neighboring regions, such as southern Arabia. Consequently, this research primarily focuses on the examination of the significance of Nabataean deities within the context of trade. It relies heavily on the study and analysis of inscriptions, artifacts, and symbols associated with selected deities. Furthermore, it involves correlating these findings with information gleaned from ancient sources and relevant texts that shed light on the multifaceted role of deities within various aspects of Nabataean society.
Keywords: Nabataeans; trade; Deities; symbols; inscriptions; temples